Anorectal malformations: Definitive management during and beyond adolescence - Sham, Minakshi (Medknow Publications & Media Pvt Ltd, 2012)
AIM: To evaluate our results of definitive repair of anorectal malformations in patients with delayed presentation, during and beyond adolescence. MATERIAL AND METHODS: It is a retrospective analysis of all adolescent patients presenting for the first time for definitive repairs and innate patients - colostomy performed during the neonatal period, but who had lost to follow-up. It includes 15 patients (2 male and 13 female) aged from 13 to 32 years. Three well-decompressed female patients were managed by primary anterior sagittal anorectoplasty (ASARP). Twelve patients underwent staged procedures. Five patients (two male and three female) underwent posterior sagittal anorectoplasty (PSARP). The oldest male patient underwent abdominal-PSARP. RESULTS: All of them attained socially acceptable fecal continence at follow-up of 1–4½ years. They are satisfied with the functional and cosmetic outcome of repair of their anomalies. CONCLUSIONS: Prospects of fecal continence are good when definitive repair of anorectal malformations is done by an expert, even in the adolescent age group and beyond.